Обзор наездников рода Gelanes (Hymenoptera, Ichneumonidae, Tersilochinae) Палеарктики - Халаим, А.И. (Вестник зоологии, 2002)
Описаны шесть новых видов палеарктического рода Gelanes Horstmann: G. belokobylskii sp. n., G. tootsae sp. n., G. bidentatus sp. n. и G. cuspidatus sp. n. с юга Дальнего Востока России, G. turkmenicus sp. n. из Туркменистана и G. gubarevae sp. n. с запада Украины. Приведены новые данные о распространении G. fusculus (Holmgren) и G. simillimus Horstmann. Дана таблица для определения всех 10 видов рода. A Review of the Species of the Genus Gelanes (Hymenoptera, Ichneumonidae, Tersilochinae) of the Palaearctic Region. Khalaim A. I. – Six new species of the Palearctic genus Gelanes Horstmann are described: G. belokobylskii sp. n., G. tootsae sp. n., G. bidentatus sp. n. and G. cuspidatus sp. n. from the south of the Russian Far East, G. turkmenicus sp. n. from Turkmenia and G. gubarevae sp. n. from the West of Ukraine. The new data on the distribution of G. fusculus (Holmgren) and G. simillimus Horstmann are represented. A key to all 10 species of the genus is given.